ANALYSIS OF THE MECHANICAL PROPERTIES BRAKE CANVAS WITH BASIC INGREDIENTS OF THE DURIAN FRUIT SKIN AND TEAK LEAVES - Masturi, Masturi; Effendy, Suhardi; Gelu, Afrianus; Hammam, Hammam; Fianti, Fianti (Universitas Negeri Semarang, 2018)
The growth of the manufacturing industry in Indonesia affects on the demand of automotive parts. This study aims see the mechanical properties of organic brake canvas made from durian fruit skin and teak leaves. Composite making was done by smoothing durian fruit and teak leaves to become powder. The resulting powder was filtered with mesh 60 so that the particle size is the same so as to facilitate mixing. After that, simple mixing with other ingredients such as magnesium oxide and polyester resin is carried out. The printing process was carried out with a hydraulic press with a load of 4 tons for 3 hours. The brake canvas produced were tested for hardness, wear resistance, and absorbency by varying the percentage composition of the powder of durian fruit fiber and teak leaves. There are five variations in the percentage of composite material composition tested. The results obtained the percentage of the most optimum composition that has a value of hardness, wear wear resistance, and absorption capacity close to the value of the Indonesian National Standard (SNI 09-0143).